Respuesta :
So,
-6p + -46 = -10
-6p - 46 = -10
Add 46 to both sides.
-6p = 36
Divide both sides by -6.
p = -6
Check.
-6(-6) + -46 = -10
36 - 46 = -10
-10 = -10
This checks.
S = {-6}
-6p + -46 = -10
-6p - 46 = -10
Add 46 to both sides.
-6p = 36
Divide both sides by -6.
p = -6
Check.
-6(-6) + -46 = -10
36 - 46 = -10
-10 = -10
This checks.
S = {-6}
for this question you should first add +46 on both sides of the equation so you will have:
-6p = -10 + 46 ⇒ -6p = 36
so now you can divide both sides by -6:
p = 36/-6 ⇒ p = -6 :)))
i hope this is helpful
have a nice day
-6p = -10 + 46 ⇒ -6p = 36
so now you can divide both sides by -6:
p = 36/-6 ⇒ p = -6 :)))
i hope this is helpful
have a nice day